Factors in Successful Collective Bargaining: Report of the Subcommittee on Labor and Labor-Management Relations, 82nd Congress, 1st Session (Relations industrielles / Industrial Relations, 1952)
The article reviews "Factors in Successful Collective Bargaining: Report" of the Subcommittee on Labor and Labor-Management Relations, 82nd Congress, 1st Session, (57 pages).